The mask of the red death: Leadership, hubris, and the Covid-19 crisis. Issue 3 (July 2021) - Villanueva, Jaume; Sapienza, Harry J
Throughout history, societies have been beset by disasters that took them by surprise, often with widespread and devastating consequences. When crops, animals, or people began dying with unusual frequency, especially when the causes were not observable, people often failed to respond, responded very slowly, or responded in surprisingly misdirected ways. In this essay, we focus on the role of leadership in addressing or failing to address such crises, paying special attention to the responses to the Covid-19 crisis during 2020. Our central thesis is that leadership hubris was a central (though not the only) culprit in poor responses, and we introduce the problem of inaction as a symptom of hubris. We conclude with some reflections for practitioners and researchers, suggesting a few areas worthy of examination to better understand how societies and business organizations may construct defenses against the dangers of leadership hubris. JEL CLASSIFICATION M14; L26; D70; N00